Republic of Moldova : Report on the Observance of Standards and Codes-Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This report assesses the Observance of Standards and Codes on Fiscal Transparency for Moldova. Moldova has made progress in recent years in improving fiscal transparency, and meets the Code of Good Practices on Fiscal Transparency in some areas. However, shortcomings remain in several areas, and key weaknesses have been identified in the monitoring of state-owned enterprises and the regulatory framework for the private sector. In a range of other areas, Moldova meets fiscal transparency requirements to some extent, but further improvements would be useful.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet